THE TIMES OF ALEXANDRU IOAN CUZA: DISCUSSIONS, PROPOSALS, PROJECTS, FAILURES AND ACHIEVEMENTS IN NATIONAL FINANCE AND BANKING - Mihai D. DRECIN (Annals: Series on History and Archaeology (Academy of Romanian Scientists), 2020)
First and foremost, we will depict the realities of “money trading” (money changing, pawnbroking, and quasi-modern lending) in the Romanian Principalities from the 18th century to mid-19th century, having as starting point a number of more ancient or recent bibliographical resources. The need for low interest rate loans to support lucrative business was increasingly present in the period between 1830 and1859. The financial market of the Romanian Principalities was becoming the focus of more and more Western European banks that were seeking to pursue business through their Ottoman branches. With the support of his close associates, Alexandru Ioan Cuza, the Ruler of the Romanian Principalities, also had in mind the modernisation of the Romanian banking system, as part of the reforms aimed at the development of the Romanian society as a whole. Discussions revolved around the establishment of a discount and circulation bank that would also have the right to issue currency and of a mortgage bank entitled to give out loans to the largest landowners in the country. Even though the 1864 establishment of the Savings and Consignments House had been successful in collecting private savings to be later used by the Government as budget resources for major national investment projects, the 1865 attempt at establishing Banque de Roumanie resulted in failure, due to opposition by the Romanian ruler’s political adversaries. The establishment of French and English banks in Romania was stopped and Romania failed to become a preferred market for Western European countries. Nevertheless, one should keep in mind that Alexandru Ioan Cuza, the Ruler of the Romanian Principalities, was a pioneer in this field as well, since his ideas were implemented and expanded upon after 1866.